A Study of Stream Sediments from Soltan Meydan Basaltic Formation Area, Northern Iran - Gahruei, Mehdi Hashemi; Gholami, Majid; Dehkordi, Teimoor Nazari (International Journal of Geography and Geology, 2013)
Stream sediments of the Eastern Alborz Mountain located at Northern Iran, were studied at Silurian-formed Soltan Meydan Basaltic Formation area. The area which is mainly consisted of basalt, andesite and tuff represents a structurally active zone, with Mountain Front Sinuosity index (Smf) of 1.2, caused development of numerous faults, prominently with NE-SW trend. Assessment of potential for metallic mineral deposits in the area was carried out using stream sediment sampling and remote sensing. Total metal concentration in the AAS-analyzed sediments varies in the range of Cu: 33-106.54 ppm, Pb: 14.46-189.04 ppm, Zn: 40.88-376 ppm, Ni: 15.14-73.24 ppm, Co: 8.2-88.64 ppm, Mn: 321.6-1326.4 ppm, and Fe: 2.28-5.39 wt%. Statistical processing of geochemical data shows two concentrated areas as geochemical anomalies. These areas are matched with those which are presented by Photo-lineament Factor (PF) indicating high density of regional structures and tectonic features. Taking high-concentrated-fractured areas into account, it is suggested that there is a close relationship between structural features and the possibility of mineralization which explains that the stream sediments could have been enriched by streams flowing through well-developed drainage system.